2010
DOI: 10.1038/sc.2010.171
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria of traumatic central cord syndrome. Part 3: Descriptive analyses of neurological and functional outcomes in a prospective cohort of traumatic motor incomplete tetraplegics

Abstract: Study design: Prospective multicenter cohort study. Objectives: To compare the neurological recovery and functional outcomes between traumatic central cord syndrome (TCCS) patients and motor incomplete tetraplegic patients. Setting: European Multicenter Study of human spinal cord injury. Methods: In 248 traumatic motor incomplete tetraplegics, initial phase (0-15 days) American Spinal Injury Association (ASIA) impairment grading, upper and lower extremity motor scores (UEMS and LEMS), upper and lower sensory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…38 Although different preclinical models can mimic the contusion like injury mechanism in humans (representing about 80% of the injuries), identifying equivalent animal models of the various human spinal cord syndromes is deficient. 39 These human SCI syndromes are characterized by unique patterns of sensorimotor impairment (specific spatial sensorimotor deficits), which have predictive value in acute traumatic SCI (ranking the cord syndromes from lowest to highest likelihood of recovery: complete cord, anterior cord, central cord, hemi cord 40 ). There are now upcoming injury models in animals (rodents and non-human primates) that are attempting to model these human cord syndromes (like lesion models of hemisection and cervical injuries), and will enable comparisons across species.…”
Section: Translation Of Outcome Measuresmentioning
confidence: 99%
“…38 Although different preclinical models can mimic the contusion like injury mechanism in humans (representing about 80% of the injuries), identifying equivalent animal models of the various human spinal cord syndromes is deficient. 39 These human SCI syndromes are characterized by unique patterns of sensorimotor impairment (specific spatial sensorimotor deficits), which have predictive value in acute traumatic SCI (ranking the cord syndromes from lowest to highest likelihood of recovery: complete cord, anterior cord, central cord, hemi cord 40 ). There are now upcoming injury models in animals (rodents and non-human primates) that are attempting to model these human cord syndromes (like lesion models of hemisection and cervical injuries), and will enable comparisons across species.…”
Section: Translation Of Outcome Measuresmentioning
confidence: 99%
“…Other studies have tended to document higher LT than PP scores for SCI subjects but have not drawn attention to any systematic differences between the two modalities. [7][8][9] Further, they have not commented on similar differences in other reports and have not discussed any relevance or reasons why such discrepancy might occur. There may be more than one reason why LT should score differently to PP.…”
Section: Discussionmentioning
confidence: 88%
“…Since its definition it was considered as a separate entity. Recently, it was shown that it is just a form of incomplete spinal cord lesion [1] therefore we abandoned the use of the term traumatic central cord syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the distinction of TCCS with an incomplete cervical spinal cord lesion (ICSCL) is artificial [1]. It is the most frequent incomplete traumatic spinal cord lesion.…”
Section: Introductionmentioning
confidence: 99%